2007
DOI: 10.1121/1.2761922
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to induced loudness reduction

Abstract: Induced loudness reduction (ILR) is a phenomenon by which a preceding higher-level tone (an inducer tone) reduces the loudness of a lower-level tone (a test tone). The strength of this effect depends on a number of parameters, reviewed here. Some of the implications of ILR on loudness data are presented via the analysis of several studies in which ILR likely resulted in otherwise unexplained biases in data sets. These results serve as examples of the pervasiveness of ILR in loudness measurements and indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The fact that our expectation induction altered loudness in Experiment 1 suggests that the gain control might be a contributor to the well-studied phenomenon called induced loudness reduction (ILR; see Epstein, 2007, for an extensive review). In ILR, a loud tone reduces the loudness of a subsequent sound at the same (or a near) frequency.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that our expectation induction altered loudness in Experiment 1 suggests that the gain control might be a contributor to the well-studied phenomenon called induced loudness reduction (ILR; see Epstein, 2007, for an extensive review). In ILR, a loud tone reduces the loudness of a subsequent sound at the same (or a near) frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have indicated that the loudness of a sound can be decreased when it is presented after a more intense sound (induced loudness reduction or loudness recalibration; see Epstein, 2007;Marozeau & Epstein, 2008). However, it seemed difficult to explain the time-stretching illusion by such loudness change, because the illusion could take place even when the noise had the same intensity as the tone and, moreover, could remain when the noise was weaker than the tone (Sasaki et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they showed no significant ILR, and they were excluded from the rest of the analysis. In previous ILR experiments, it has not been uncommon to find listeners that did not show any ILR (Epstein, 2007). Figure 2 shows the amount of ILR for each listener, estimated as the average of the three inducer conditions subtracted from the average of the three baseline conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Because the effects of ILR accumulate over time, results obtained in the early portions of experiments, prior to significant sound exposure, may differ markedly from results obtained in later portions of experiments (Arieh, Kelly, & Marks, 2005). Epstein (2007) examined the results of a magnitude estimation study by Hellman and Zwislocki (1963). The magnitude estimation data indicated that over the course of the experiment, loudness changed more for moderate-level sounds than it did for low-and high-level sounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation